DARI BUKIT CINTA MENUJU PANGGUNG PENCITRAAN OBJEK WISATA BUKIT CINTA - Richard Mayopu (Jurnal Ilmu Komunikasi Acta Diurna, 2017)
Understanding of "imaging" has often been heard or known by the wider community is no exceptionto the people of Indonesia. By seeing and referring to the news that is often broadcast by the massmedia, imaging becomes a very important thing in the life of modern society. This study aims toprovide an understanding of the imaging process that has been dominating (imaging formed in aplanned and structured) that turned out to be contrary to the facts and reality. The example of thecase used is tourism destination in the district of Semarang named Bukit Cinta. This Research willbe focused on the process of the meaning image (Citra) based on the myth that is believed by thepublic around Bukit Cinta. Research using qualitative research methods that will discuss in depthabout the meaning process of an image which will help the authors to develop new conceptsrelated to the concept of imaging itself. Learning from the experience and early findings of thisresearch, the authors believe that the image can be “set up” but at the same time, the image canalso occur without any element of deliberation or setting.